Langkah Kecilku Menuju Kebahagiaan: Efektivitas Lari Laun Bersama terhadap Happiness - Zidan Maliki Akbar; Tuti Rahmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
In human life, sports play a very important role as they can influence both physical and psychological conditions. Through regular physical activity, individuals not only achieve physical fitness but also maintain mental and emotional balance. One type of exercise that is interesting to study is slow running, which involves running at a steady but gentle pace. This study focuses on examining the effectiveness of group slow running on levels of happiness. The subjects of this research were students from the Psychology Department at Universitas Negeri Padang, class of 2021, aged between 18 and 21 years old. The study employed a quantitative method with an experimental approach using a pretest-posttest control group design. Two groups were involved in this research—an experimental group and a control group—each receiving different treatments. Measurements were conducted before and after the intervention to observe changes in happiness levels. The results of the independent sample t-test analysis showed a significance value of 0.003, which is smaller than α = 0.05. This indicates a significant difference between the two groups. Therefore, it can be concluded that group slow running is effective in increasing happiness among adolescents, particularly university students, as it fosters feelings of relaxation, enthusiasm, and togetherness.